Analisis Perilaku Petani Padi Rawa Lebak dan Hubungannya dengan Produksi dan Pendapatan di Kelurahan Sei Lais Kecamatan Kalidoni Kota Palembang - Sriati Sriati; Nukmal Hakim; Adityo Nugraha (Seminar Nasional Lahan Suboptimal, 2019)
Sriati S, Hakim N, Nugraha A. 2019. Behavior analysis of  swamp rice farmers and their correlation with production and income in Sungai Lais Village Kalidoni Sub-District Palembang City. In: Herlinda S et al. (Eds.), Prosiding Seminar Nasional Lahan Suboptimal 2019, Palembang 4-5 September 2019. pp. 452-458.  Palembang: Unsri Press.The objectives of this study were: (1) to describe the behavior of farmers swamp rice farming (2) to calculate the production and income of swamp rice farmers, and (3) to analyze the correlation between behavior with production and income of swampy rice farmers. The study was done at Sei Lais with the survey method. Samples taken randomly amounted to 35 people from the population of 263 people. Data consists of primary and secondary data. Data processed by tabulation then analyzed descriptively, and analysis of the correlation between behavior with production and income was carried out by the Spearman Rank Correlation Test. The results of the study showed that: (1) The behavior of farmers in handling Swamp rice was of moderate criteria, with an average score of 31.74 (70.53% of the ideal value). (2) Rice production averages 3172 kg/lg/yr, and the average income is Rp. 8,653,514.29;  and (3) There is a significant positive correlation between farmer's behavior with production and income, both of correlation value in the category is medium tightly. The correlation between behavior with rice production with the value of the correlation coefficient Rs = 0.425 significant at α = 0.05; and the correlation between behavior and farmer income with a correlation coefficient value of Rs = 0.457 significant at α = 0.01. While the correlation between rice production and farmer's income has a high correlation coefficient (very close), with a value of Rs = 0, 977 significant at α = 0.01.Keywords: farmer behaviour, income, production, swamp rice